Pendampingan Manajemen Usaha dan Pemasaran Melalui Aplikasi ChickFinTrack Bagi Kelompok Rumah Potong Ayam Desa Tunggulwulung - Cahya Bagus Sanjaya; Nuriyanto; Kholid Murtadlo; Imronrosadi Rosadi (Jurnal Pemberdayaan Masyarakat, 2025)
The community service program in Tunggulwulung village, Pasuruan district, addressed the financial management and marketing challenges faced by the Chicken Slaughterhouse (RPA), which previously relied on manual processes. The solution implemented was the application of ChickFinTrack for financial management and digital marketing. Using the Participatory Action Research (PAR) method, this approach included stages of socialization, training, technology implementation, application usage assistance, and evaluation. The results of this activity show that financial management and marketing have become more accurate, efficient, and easier to monitor online. Financial reports are generated automatically, while marketing has been improved through digital catalogs, social media promotions, and online ordering. This program has significantly increased the partners' understanding of finance and marketing, making them more effective and sustainable.